Peran Unit Lost And Found Dalam Penanganan Bagasi Bermasalah Pada Maskapai Citilink Di PT Gapura Angkasa Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Rahimudin; Widiya Afni Aprilia (Populer: Jurnal Penelitian Mahasiswa, 2023)
The Lost and Found Unit is a work unit that has duties and responsibilities in handling passenger luggage. If there is a problem with the passenger's baggage, the passenger can immediately report it to the Lost and Found unit so that efforts are made to handle it. In serving the Lost and Found unit, it hopes to deal directly with passengers, so of course the service provided must be better. The purpose of this research is to find out the procedures for handling Delayed Baggge, damaged baggage by Lost and Found unit officers, factors causing problems and what efforts are made by Lost and Found unit officers in order to reduce the occurrence of cases. This study used a qualitative method with data collection in the form of observation, interviews and documentation, in which this study interviewed 5 informants from the Lost and Found unit officers. The results of this study indicate that Lost and Found unit officers have followed Standard Operational Procedures (SOP) and Job Desks in handling cases of Delayed Baggage and damaged baggage. Factors that cause problems include Human Error, Check In Counter, Airport Facilities, Make Up Area, Loading and Unloading processes, Misrouted, minimum Connection time and passenger baggage. Efforts made by Lost and Found unit officers in order to reduce the occurrence of cases by controlling every activity and reminding officers to be more careful, thorough and focused when doing work. Officers must prioritize Safety and Security and comply with the established SOP.